Anti-dispersion grouting material based on coal-based solid waste as well as preparation method and application of anti-dispersion grouting material

By optimizing the activation technology of coal-based solid waste and the material compounding process, a dispersion-resistant grouting material based on coal-based solid waste is developed, and components such as alkali exciters and cellulose are used to solve the problem of easy dispersion of traditional grouting materials and storage of coal-based solid waste, achieving high strength, dispersion resistance and resource utilization.

CN119569385AActive Publication Date: 2025-03-07ANHUI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411784557.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Traditional underwater grouting materials are easily dispersed under the impact and dissolution of water flow, and have low early strength, resulting in unsatisfactory reinforcement effect and waste of materials, increasing construction difficulty and engineering costs. At the same time, the problem of coal-based solid waste storage needs to be solved urgently.

Method used

By optimizing the activation technology of coal-based solid waste and the material compounding process, an anti-dispersion grouting material based on coal-based solid waste is developed, and the potential activity of coal-based solid waste is stimulated by alkali excitation agents, and a high-strength gel and framework structure are generated, and the anti-dispersion performance of the material is improved through the combination of cellulose and water glass.

Benefits of technology

It significantly improves the early strength and curing speed of the material, improves the underwater dispersion resistance, ensures the quality and reliability of grouting construction, and at the same time realizes the resource utilization of solid waste, reducing environmental pollution and resource waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569385A_ABST
    Figure CN119569385A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid waste recycling, and provides an anti-dispersion grouting material based on coal-based solid waste and a preparation method and application thereof.The anti-dispersion grouting material is prepared from coal gangue, fly ash, silica fume, cellulose, a water reducing agent and an alkali activator, and the alkali activator is prepared from deionized water, sodium hydroxide and water glass. The anti-dispersion grouting material based on the coal-based solid waste is prepared according to the following steps: mixing coal gangue, fly ash, silica fume, cellulose and a water reducing agent, and stirring to prepare a powder precursor; an alkali activator is added into the prepared powder precursor, the alkali activator is prepared from deionized water, sodium hydroxide and water glass, stirring continues to be conducted, and the anti-dispersion grouting material based on the coal-based solid waste is prepared. The anti-dispersion grouting material with excellent fluidity, stability and mechanical properties can be prepared, an innovative path is provided for recycling of coal-based solid waste, the material cost is remarkably reduced, and the environmental protection benefit and the engineering application value are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste recycling, and in particular to an anti-dispersion grouting material based on coal-based solid waste, and a preparation method and application thereof. Background Art

[0002] Grouting reinforcement is an important technical means to prevent and control mine water hazards and improve geological conditions. It is widely used in underground engineering and the reinforcement of broken rock masses in mines. At present, grouting reinforcement technology has become one of the main solutions to solve the problem of instability and damage of broken rock masses in underground engineering. However, in practical applications, traditional underwater grouting materials are often affected by water flow impact and dissolution, and often have problems such as easy dispersion, low early strength, and material loss. This not only leads to unsatisfactory grouting effects, but also causes material waste, while increasing construction difficulty and engineering costs.

[0003] At the same time, the large-scale storage of coal-based solid waste has become an environmental and resource utilization issue that needs to be solved urgently. If these solid wastes are not effectively utilized, they will not only occupy a large amount of land resources, but may also cause pollution and damage to the ecological environment. However, coal-based solid waste, due to its unique chemical composition and potential gelling properties, provides a good foundation for the development of new functional building materials.

[0004] Therefore, how to develop a grouting material with excellent anti-dispersion performance and high early strength based on coal-based solid waste by optimizing the activation technology and material compounding process of coal-based solid waste has become a key technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of this, in order to overcome the deficiencies of the prior art, the present invention aims to provide an anti-dispersion grouting material based on coal-based solid waste, and a preparation method and application thereof.

[0006] According to a first aspect of the present invention, there is provided an anti-dispersion grouting material based on coal-based solid waste, the material being made from coal gangue, fly ash, silica fume, cellulose, a water reducer and an alkali activator, wherein the alkali activator is made from deionized water, sodium hydroxide and water glass.

[0007] Preferably, the anti-dispersion grouting material based on coal-based solid waste of the present invention is prepared according to the following steps: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 5-10 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator is added to the prepared powder precursor, wherein the alkali activator is prepared from 471.6-585.5 parts by weight of deionized water, 29.2-58.4 parts by weight of sodium hydroxide and 270-370 parts by weight of water glass, and stirring is continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0008] Preferably, in the anti-dispersion grouting material based on coal-based solid waste of the present invention, the water reducer is a polycarboxylate water reducer for improving the slurry with a bulk density of 500-550 g / L, a solid content greater than 98%, and a water reduction rate greater than 15%.

[0009] Preferably, in the anti-dispersion grouting material based on coal-based solid waste of the present invention, the cellulose is hydroxyethyl methyl cellulose, and the main chain of the hydroxyethyl methyl cellulose is composed of glucose units connected by β-1,4-glycosidic bonds.

[0010] Preferably, in the anti-dispersion grouting material based on coal-based solid waste of the present invention, the modulus of water glass is 3.2, the solid content is 40%, the Baume degree is 40, and the pH value is 9.

[0011] According to a second aspect of the present invention, there is provided a method for preparing an anti-dispersion grouting material based on coal-based solid waste, the method comprising: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 5-10 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator is added to the prepared powder precursor, wherein the alkali activator is prepared from 471.6-585.5 parts by weight of deionized water, 29.2-58.4 parts by weight of sodium hydroxide and 270-370 parts by weight of water glass, and stirring is continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0012] Preferably, in the method for preparing the anti-dispersion grouting material based on coal-based solid waste of the present invention, the water reducer is a polycarboxylic acid water reducer with a bulk density of 500-550 g / L, a solid content greater than 98%, and a water reduction rate greater than 15%.

[0013] Preferably, in the method for preparing anti-dispersion grouting materials based on coal-based solid waste of the present invention, the cellulose is hydroxyethyl methyl cellulose, and the main chain of the hydroxyethyl methyl cellulose is composed of glucose units connected by β-1,4-glycosidic bonds.

[0014] Preferably, in the method for preparing the anti-dispersion grouting material based on coal-based solid waste of the present invention, the modulus of water glass is 3.2, the solid content is 40%, the Baume degree is 40, and the pH value is 9.

[0015] According to a third aspect of the present invention, there is provided an application of an anti-dispersion grouting material based on coal-based solid waste as a grouting material for underwater engineering.

[0016] The anti-dispersion grouting material based on coal-based solid waste and its preparation method and application have the following beneficial technical effects: 1. Improve mechanical properties: Active components and an appropriate amount of alkali activator are introduced into the material. By regulating the mineral composition and reaction system and stimulating the potential activity of coal-based solid waste through the alkali activator, high-strength gel and skeleton structure are generated, which significantly improves the early strength and curing speed of the material. Compared with traditional underwater grouting materials that rely on cement as a gelling material, the alkali activation technology in the present invention not only reduces the amount of cement used, but also improves the mechanical properties of the material, and can quickly achieve reinforcement effects, meeting the needs of rapid reinforcement of mines and underground projects.

[0017] 2. Improve underwater anti-dispersion performance: By optimizing the activation and compounding process of coal-based solid waste, the material has strong anti-dispersion performance in the underwater environment, effectively avoiding the dispersion problem of traditional grouting materials under water impact or dissolution, and avoiding the reduction of reinforcement effect of traditional grouting materials due to dispersion, thus ensuring the quality and reliability of grouting construction.

[0018] 3. Resource utilization and environmental friendliness: With coal gangue, fly ash and silica fume as the main raw materials, the active ingredients in coal-based solid waste are effectively utilized, the resource utilization of solid waste is realized, the dependence on natural resources is reduced, the cost of raw materials is reduced, and the environmental storage pressure of coal-based solid waste is alleviated; no high-temperature calcination or high-energy-consuming process is required in the preparation process, which reduces carbon emissions and energy consumption. By using alkali activators to replace part of the cement, the carbon emissions in the production process are significantly reduced, which helps to alleviate environmental pollution and resource waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is a test diagram of the anti-dispersion grouting material based on coal-based solid waste prepared in Example 9 of the present invention under dynamic water conditions; Figure 2 Schematic diagram of the effect of the interaction between cellulose and water glass on the 7-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention; Figure 3Schematic diagram of the effect of the interaction between cellulose and sodium hydroxide on the 7-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention; Figure 4 Schematic diagram of the effect of the interaction between sodium hydroxide and water glass on the 7-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention; Figure 5 Schematic diagram of the effect of the interaction between cellulose and water glass on the 28-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention; Figure 6 Schematic diagram of the effect of the interaction between water glass and sodium hydroxide on the 28-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention; Figure 7 Schematic diagram of the effect of the interaction between sodium hydroxide and water glass on the 28-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention. DETAILED DESCRIPTION

[0021] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0022] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.

[0023] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.

[0024] The components and contents of the coal gangue, fly ash and silica fume used in the embodiments of the present invention are shown in Table 1 below.

[0025] Table 1

[0026] The water reducer used in the embodiment of the present invention is a polycarboxylate water reducer with a bulk density of 500-550g / L, a solid content of greater than 98%, and a water reduction rate of greater than 15%; the cellulose is hydroxyethyl methyl cellulose, and the main chain of the hydroxyethyl methyl cellulose is composed of glucose units connected by β-1,4-glycosidic bonds; the modulus of water glass is 3.2, the solid content is 40%, the Baume degree is 40, and the pH value is 9.

[0027] Example 1 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 7.5 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 584.2 parts by weight of deionized water, 45.8 parts by weight of sodium hydroxide and 270 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0028] Example 2 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 5 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 583.1 parts by weight of deionized water, 36.9 parts by weight of sodium hydroxide and 280 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0029] Example 3 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 10 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 583.1 parts by weight of deionized water, 36.9 parts by weight of sodium hydroxide and 280 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0030] Example 4 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 7.5 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 584.2 parts by weight of deionized water, 45.8 parts by weight of sodium hydroxide and 270 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0031] Example 5 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 5 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 537.5 parts by weight of deionized water, 52.5 parts by weight of sodium hydroxide and 310 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0032] Example 6 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 5 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 536.2 parts by weight of deionized water, 33.8 parts by weight of sodium hydroxide and 330 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0033] Example 7 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 10 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 537.9 parts by weight of deionized water, 42.1 parts by weight of sodium hydroxide and 320 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0034] Example 8 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 10 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 536.2 parts by weight of deionized water, 33.8 parts by weight of sodium hydroxide and 330 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0035] Example 9 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 7.5 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 537.5 parts by weight of deionized water, 52.5 parts by weight of sodium hydroxide and 310 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0036] Example 10 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 7.5 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 471.6 parts by weight of deionized water, 58.4 parts by weight of sodium hydroxide and 345 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0037] Embodiment 11 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 7.5 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 492.1 parts by weight of deionized water, 37.9 parts by weight of sodium hydroxide and 370 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0038] Example 12 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 5 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 492.6 parts by weight of deionized water, 47.4 parts by weight of sodium hydroxide and 360 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0039] Embodiment 13 An anti-dispersion grouting material based on coal-based solid waste, the preparation steps of which are as follows: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 10 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator was added to the prepared powder precursor, wherein the alkali activator was prepared from 492.6 parts by weight of deionized water, 47.4 parts by weight of sodium hydroxide and 360 parts by weight of water glass, and stirring was continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

[0040] Embodiment 14 The initial setting time and final setting time of the anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 13 were determined by using an ISO standard Vicat instrument; the fluidity of the anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 13 was tested by using a standard fluidity measuring platform, and the standard fluidity measuring platform used a standard truncated cone mold (upper opening diameter of 36 mm, lower opening diameter of 60 mm, height of 60 mm) and a glass plate; the viscosity of the anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 13 was measured by using an NDJ-4 rotary viscometer; the dynamic water retention rate of the anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 13 was measured by using an anti-dispersion test device; the compressive strength of the anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 13 was tested under standard curing and underwater molding curing conditions, and the water-to-land strength ratio was calculated; the above test and calculation results are shown in Table 2 below.

[0041] Table 2

[0042] As shown in Table 2, when preparing anti-dispersion grouting materials based on coal-based solid waste in Examples 1-13 of the present invention, when the mass fraction of water glass is low, the final setting time is long, such as high values ​​such as 675min and 780min; when the mass fraction of water glass is high, the final setting time is significantly reduced, and the lowest values ​​are 302min and 320min, etc., showing a faster setting speed. In the preparation of the embodiments of the present invention, water glass has a significant effect on the setting time. While balancing the setting speed and operability, the setting speed can be significantly accelerated by appropriately adding water glass to meet different engineering requirements.

[0043] As shown in Table 2, when preparing anti-dispersion grouting materials based on coal-based solid waste in Examples 1-13 of the present invention, the more parts by weight of water glass, the more silicate ion content in the system, and the more dense network structure is formed. This network structure will increase the viscosity of the slurry and reduce the fluidity. The cellulose in the embodiments of the present invention can improve the fluidity and stability of the slurry. It helps the suspension of slurry particles by swelling in water, thereby improving the fluidity, especially in systems with higher modulus. It can play a buffering role, which can not only improve the fluidity, but also improve the anti-dispersion and stability of the slurry, so that it performs better underwater or in a humid environment.

[0044] Figure 1 This is a test diagram of the anti-dispersion grouting material based on coal-based solid waste prepared in Example 9 of the present invention under dynamic water conditions, as shown in Figure 1 As shown in Table 2, the anti-dispersion grouting material based on coal-based solid waste has a dynamic water retention rate of more than 75% under dynamic water conditions. The present invention regulates the performance of the anti-dispersion grouting material based on coal-based solid waste by component ratio and material selection. In the anti-dispersion grouting material based on coal-based solid waste of the embodiment of the present invention, the cellulose molecular structure contains a long chain structure, which has an adsorption effect and can be adsorbed on the surface. This connection effect enables the slurry to resist the erosion of dynamic water as a whole, which can significantly improve the anti-erosion performance of the material.

[0045] Figure 2 Schematic diagram of the effect of the interaction between cellulose and water glass on the 7-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention, as shown in FIG. Figure 2 As shown in Table 2, with the increase of cellulose content, the anti-dispersion and operability of the anti-dispersion grouting material based on coal-based solid waste are improved, and the water-to-land strength ratio of the material is always maintained in a relatively ideal range; with the increase of water glass content, silicate ions form a denser network structure, which is conducive to the formation of a dense gel, and the water-to-land strength ratio of the material increases.

[0046] Figure 3Schematic diagram of the effect of the interaction between cellulose and sodium hydroxide on the 7-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention, as shown in FIG. Figure 3 As shown in Table 2, sodium hydroxide can increase the solubility of silicon oxides and aluminum oxides in solid waste materials, promote the hydration reaction, thereby accelerating the formation of a stronger polymer network and improving the strength of the material. At the same time, the increase in sodium hydroxide helps to form more gel phases, and these gels can enhance the structural stability of the material during the hydration reaction.

[0047] Figure 4 Schematic diagram of the effect of the interaction between sodium hydroxide and water glass on the 7-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention, as shown in FIG. Figure 4 As shown in Table 2, with the decrease of sodium hydroxide, the relative proportion of silicate ions increases, and the accompanying increase of water glass further enhances the activity of the hydration reaction. This combination can effectively promote the formation of gel in the material, increase the density, and thus improve the water-land strength ratio.

[0048] Figure 5 Schematic diagram of the effect of the interaction between cellulose and water glass on the 28-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention, as shown in FIG. Figure 5 As shown in Table 2, with the increase of cellulose content, the water-land strength ratio shows a gradually increasing trend. This is because cellulose effectively inhibits water loss, allowing the material to solidify more evenly during the curing process, thereby enhancing the overall strength. At the same time, the higher the mass fraction of water glass, the more evenly it can be distributed, reducing the phenomenon of rapid gel solidification, which helps to improve the water-land strength ratio.

[0049] Figure 6 Schematic diagram of the effect of the interaction between water glass and sodium hydroxide on the 28-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention; Figure 6 As shown in Table 2, Figure 6 From the edge to the middle convex area, the strength performance of the anti-dispersion grouting material based on coal-based solid waste continues to improve. The combination of cellulose and sodium hydroxide corresponding to the middle convex area works together to achieve the optimal water-land strength ratio. The right amount of cellulose can improve the adhesion of the material, thereby increasing the underwater strength and the water-land strength ratio. The addition of sodium hydroxide can improve the sol-gel reaction efficiency of the material and enhance the generation of hydration products.

[0050] Figure 7 Schematic diagram of the effect of the interaction between sodium hydroxide and water glass on the 28-day water-to-land strength ratio of the anti-dispersion grouting material based on coal-based solid waste in Examples 1-13 of the present invention, as shown in FIG. Figure 7As shown in Table 2, the surface forms a higher peak near the middle mass fraction of sodium hydroxide and the higher mass fraction of water glass, indicating that the water-to-land strength ratio is close to or greater than 1 under this ratio, and the performance is superior. The water-to-land strength ratio corresponding to the peak point is about 1.2-1.6, indicating that under this condition, the strength of the material in the underwater environment is close to or even higher than that in the land environment.

[0051] The anti-dispersion grouting material based on coal-based solid waste and the preparation method thereof according to the embodiment of the present invention have the following beneficial technical effects: 1. Improve mechanical properties: Active components and an appropriate amount of alkali activator are introduced into the material. By regulating the mineral composition and reaction system and stimulating the potential activity of coal-based solid waste through the alkali activator, high-strength gel and skeleton structure are generated, which significantly improves the early strength and curing speed of the material. Compared with traditional underwater grouting materials that rely on cement as a gelling material, the alkali activation technology in the present invention not only reduces the amount of cement used, but also improves the mechanical properties of the material, and can quickly achieve reinforcement effects, meeting the needs of rapid reinforcement of mines and underground projects.

[0052] 2. Improve underwater anti-dispersion performance: By optimizing the activation and compounding process of coal-based solid waste, the material has strong anti-dispersion performance in the underwater environment, effectively avoiding the dispersion problem of traditional grouting materials under water impact or dissolution, and avoiding the reduction of reinforcement effect of traditional grouting materials due to dispersion, thus ensuring the quality and reliability of grouting construction.

[0053] 3. Resource utilization and environmental friendliness: With coal gangue, fly ash and silica fume as the main raw materials, the active ingredients in coal-based solid waste are effectively utilized, the resource utilization of solid waste is realized, the dependence on natural resources is reduced, the cost of raw materials is reduced, and the environmental storage pressure of coal-based solid waste is alleviated; no high-temperature calcination or high-energy-consuming process is required in the preparation process, which reduces carbon emissions and energy consumption. By using alkali activators to replace part of the cement, the carbon emissions in the production process are significantly reduced, which helps to alleviate environmental pollution and resource waste.

[0054] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. An anti-dispersion grouting material based on coal-based solid waste, characterized in that: The material is prepared from coal gangue, fly ash, silica fume, cellulose, a water reducing agent and an alkali activator, wherein the alkali activator is prepared from deionized water, sodium hydroxide and water glass.

2. The anti-dispersion grouting material based on coal-based solid waste according to claim 1, characterized in that: The material is prepared according to the following steps: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 5-10 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator is added to the prepared powder precursor, wherein the alkali activator is prepared from 471.6-585.5 parts by weight of deionized water, 29.2-58.4 parts by weight of sodium hydroxide and 270-370 parts by weight of water glass, and stirring is continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

3. The anti-dispersion grouting material based on coal-based solid waste according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent with a bulk density of 500-550 g / L, a solid content greater than 98%, and a water reducing rate greater than 15%.

4. The anti-dispersion grouting material based on coal-based solid waste according to claim 1, characterized in that: The cellulose is hydroxyethyl methyl cellulose, and the main chain of the hydroxyethyl methyl cellulose is formed by glucose units connected by β-1,4-glycosidic bonds.

5. The anti-dispersion grouting material based on coal-based solid waste according to claim 1, characterized in that: The modulus of water glass is 3.2, the solid content is 40%, the Baume degree is 40, and the pH value is 9.

6. A method for preparing an anti-dispersion grouting material based on coal-based solid waste, characterized in that: The method comprises: Step 1: Preparation of powder precursor 500 parts by weight of coal gangue, 200 parts by weight of fly ash, 300 parts by weight of silica fume, 5-10 parts by weight of cellulose and 5 parts by weight of a water reducing agent were mixed and stirred for 5 minutes to obtain a powder precursor; Step 2: Preparation of anti-dispersion grouting materials based on coal-based solid waste An alkali activator is added to the prepared powder precursor, wherein the alkali activator is prepared from 471.6-585.5 parts by weight of deionized water, 29.2-58.4 parts by weight of sodium hydroxide and 270-370 parts by weight of water glass, and stirring is continued for 3 minutes to obtain an anti-dispersion grouting material based on coal-based solid waste.

7. The method for preparing the anti-dispersion grouting material based on coal-based solid waste according to claim 6, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent with a bulk density of 500-550 g / L, a solid content greater than 98%, and a water reducing rate greater than 15%.

8. The method for preparing the anti-dispersion grouting material based on coal-based solid waste according to claim 6, characterized in that: The cellulose is hydroxyethyl methyl cellulose, and the main chain of the hydroxyethyl methyl cellulose is formed by glucose units connected by β-1,4-glycosidic bonds.

9. The method for preparing the anti-dispersion grouting material based on coal-based solid waste according to claim 6, characterized in that: The modulus of water glass is 3.2, the solid content is 40%, the Baume degree is 40, and the pH value is 9.

10. An application of an anti-dispersion grouting material based on coal-based solid waste, characterized in that: The use of the anti-dispersion grouting material based on coal-based solid waste as described in any one of claims 1 to 5 as an underwater engineering grouting material.